Quantitative risk assesment of benzene exposure in printing industry x Surabaya city - Habibati, Amanda Fithri; Tualeka, Abdul Rohim; Jalaludin, Juliana; Russeng, Syamsiar; Ahsan; Rahmawati, Puji (Institute of Medico-legal Publications Private Limited, 2021)
Benzene is a compound chemically volatile and lasts a long time in the air and quicklyinhaled into the human body. The use of benzene is widely used in various industries, one ofwhich is the printing industry. Benzene produced right in the printing industry are ink, cleaning fluid,and when the machine in operation. Workers exposed to benzene can risk cancer and non-cancer healtheffects that are harmful to the human body. This study aimed to assess cancer and non-cancer risk ofworkers in the printing industry X Surabaya City. This research is observational, cross-sectional withthe same sample with a total population of 11 workers in the printing industry X Surabaya City. Therisk assessment method uses four stages: hazard identification, exposure analysis, dose and responseanalysis, and risk characterization. This research shows that the average concentration of benzene is1.0729 mg/m3 or 0.34 ppm. RQ value > 1 both real-time and lifetime. As many as 63.6% of workershave real-time ECR >10 -4, and 81.8% of workers have ECR lifetime >10-4. This study concludes thatworkers are in an unsafe condition and have non-carcinogenic and carcinogenic health risks.